PEMANFAATAN TEKNOLOGI INDERAJA UNTUK PENINGKATAN EKONOMI NELAYAN DI DESA LILIBOY - Hukubun, Ronald D; Saleky, Valentine D; Soukotta, Imanuel V T; Wattimena, Marlin Ch; Kalay, Degen E (Balobe: Jurnal Pengabdian Masyarakat, 2022)
Remote sensing technology has developed very rapidly and has a very significant role in the fisheries and marine sector as a provider of data and information. Liliboy Country is a coastal village located on the island of Ambon which has very productive waters with potential for fishing activities. This Community Service is made in the form of counseling, with the aim of introducing technological knowledge and providing information about fishing areas, as well as developing skills for the fishermen of Liliboy village to get more effective and efficient catches. It is hoped that the fishing community of Liliboy village will understand the use of sensing technology to determine fishing areas so that it will grow the community's economy and improve the welfare of life